2001
DOI: 10.3923/jbs.2001.363.364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transplanting Dates on Yield and its Related Traits in Rice (Oriza sativa L.)

Abstract: Study envisaged that early planted (May,16) rice taken greater days to heading (110.4 days), maturity (136.0 days) and plant height (102.25 cm). However, number of panicles/hill (19.75), grains/panicle (109), grain weight/hill (79.13 g), 1000 grain weight (36.10 g) and grain yield (5750 kg haG 1) were significantly greater in 1 st June planted rice. Thus, it is recommended that transplanting during the first week of June is ideal for achieving maximum grain yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This might be due to sufficient time to stay in the field of rice plants which facilitated the plants to improve their photosynthesis activities which in turn caused the tallest plants. Alike results were also depicted by Soomro et al (2001) and Nila et al (2018) who found taller plants in early transplanting than in late transplanting. Plant height tends to decrease due to delay in transplanting (Table 1).…”
Section: Effect Of Date Of Transplantingsupporting
confidence: 59%
“…This might be due to sufficient time to stay in the field of rice plants which facilitated the plants to improve their photosynthesis activities which in turn caused the tallest plants. Alike results were also depicted by Soomro et al (2001) and Nila et al (2018) who found taller plants in early transplanting than in late transplanting. Plant height tends to decrease due to delay in transplanting (Table 1).…”
Section: Effect Of Date Of Transplantingsupporting
confidence: 59%
“…Khalifa (2009) also reported the similar results showing early date of transplanting is the best time of transplanting to gain important yield attributing characters. A large number of productive tillers in early transplanting may be attributed to favorable environmental factors that may have provided optimum weather for enhanced plant growth and production relative to other transplanting dates, the contrasting results were also reported by Soomro et al (2001). The interaction of cultivars and dates of transplanting showed significant results for effective tillers m -2 , grain yield, grains panicle -1 , and test weight whereas non-significant results were observed for weight of panicle and sterility percentage (Table 6).…”
Section: Effects Of Cultivars and Transplanting Dates On Yield And Yi...mentioning
confidence: 94%